Azadirachta indica (Sapindales: Meliaceae) Neem Oil as a Repellent Against Aedes albopictus (Diptera: Culicidae) Mosquitoes. Issue 6 (25th November 2019) - Macchioni, Fabio; Sfingi, Marta; Chiavacci, Daniele; Cecchi, Francesca
Abstract: Increased concerns regarding the safety of many chemicals used as insecticides or repellents, together with the development of resistance by insects to various insecticides, have led to the search for new active natural ingredients. For what we believe is the first time, that is monitored the efficiency of neem oil ( Azadirachta indica ) as a repellent against adult Aedes albopictus directly in the field. To test the efficacy of repellency against adults, treatments were performed (5 ml/l) in six different locations. For each location, two closed gardens distance between them 200 m were chosen (one where the treatment was performed, consisting in spraying a mixture of water and Neem oil 5 g/l and one which was used as a control where only water with emulsifier was used). To monitor the treatment efficacy, six ovitraps were used (for each location three for the treated garden and three for the control garden). Data (n° mosquito eggs trapped in each ovitrap) were collected weekly for 6 mo (from May to October) for a total of 900 samplings. Daily temperature and daily rainfall were monitored throughout the trial. The treatment was most effective in June and July. Very high temperatures and high rainfall reduced the efficacy of neem oil over time.